Magnetic anisotropy of chloritoid. Issue 8 (6th August 2013) - Haerinck, Tom; Debacker, Timothy N.; Sintubin, Manuel
Abstract : [1] The magnetocrystalline anisotropy of monoclinic chloritoid, a relatively common mineral in aluminum‐rich, metapelitic rocks, has been determined for the first time by measuring the high‐field anisotropy of magnetic susceptibility (HF‐AMS), using two independent approaches, i.e., (a) directional magnetic hysteresis measurements and (b) torque magnetometry, on a collection of single crystals collected from different tectonometamorphic settings worldwide. Magnetic remanence experiments show that all specimens contain ferromagnetic ( s.l .) impurities, being mainly magnetite. The determined HF‐AMS ellipsoids have a highly oblate shape with the minimum susceptibility direction subparallel to the crystallographic c‐axis of chloritoid. In the basal plane of chloritoid, though the HF‐AMS can be considered isotropic. The degree of anisotropy is found to be 1.47, which is significantly higher than the anisotropy of most paramagnetic silicates and even well above the frequently used upper limit (i.e., 1.35) for the paramagnetic contribution to the AMS of siliciclastic rocks. The obtained values for the paramagnetic Curie temperature parallel (θ ∥ ) and perpendicular (θ ⊥ ) to the basal plane indicate that this pronounced magnetocrystalline anisotropy is related to strong antiferromagnetic exchange interactions in the direction of the crystallographic c‐axis (θ ⊥  < 0) and rather weak ferromagnetic exchange interactions within the basal plane (θ ∥ > 0). As a consequence, chloritoid‐bearing metapelites with a pronounced mineral alignment can have a high degree of anisotropy without the need of invoking a significant contribution of strongly anisotropic, ferromagnetic ( s.l .) minerals. The newly discovered magnetocrystalline anisotropy of chloritoid thus calls for a revised approach of magnetic fabric interpretations in chloritoid‐bearing rocks. Key Points: The AMS of chloritoid is highly oblate and strongly anisotropic (PJ = 1.47) The chloritoid AMS is clearly higher than that of other paramagnetic silicates. The newly discovered values call for a revision of the paramagnetic upper limit